Guidelines for ethno-centric psychosocial management of diabetes mellitus in India: The north east consensus group statement - Kalra, Sanjay; Baruah, Manash P.; Ranabir, Salam; Singh, Ningthoujam Biplam; Choudhury, Asit Baran; Sutradhar, Satish; Adhikari, Santosh; Dehingia, Ananda; Mili, Dambaru Dhar; Hesso, Kevito; Rasaily, Suresh Madan; Dkhar, Andreas; Roy, Partho; Majumder, Shahnowaj; Ahmed, Rahimuddin (Journal of Social Health and Diabetes, 2013)
Recently published guidelines on Psychosocial Management of Diabetes in India provide evidence-based recommendations for the whole nation. However, they do not fully address the myriad socio-cultural issues prevalent in the North Eastern states. The eight North Eastern states of India house 45 million people, belonging to 220 ethnic groups who speak an equal number of dialects, and follow distinctly unique cultures, which impact health-related behavior. Such diversity is difficult to cover in any national guideline. This lacuna makes it necessary to have a document, which addresses the specific needs and requirements of diabetes care professionals in the North-east of India. This consensus statement aims to highlight evidence- and experience-based strategies for psychosocial management of diabetes, based upon the unique ethnographic constitution of this part of the country. It is based upon the results of a daylong focused group discussion, held at Sonapur, Assam, on 9th February 2013, involving key opinion leaders from most North-eastern states, including all geographical divisions of Assam. Recommendations are classified into three domains: General, psychological, and socio-cultural, and graded by the weight they should have in clinical practice. Eighteen recommendations of varying strength are made, to help professionals identify the psycho-socio-cultural determinants of diabetes, and to explore the role of psycho-socio-cultural interventions in devising support strategies for people with diabetes and their families. They also aid in developing core skills needed for effective diabetes management. These recommendations provide practical guidelines to fulfill unmet needs in diabetes management in the North-east and help achieve a qualitative improvement in diabetes care. The guidelines may also be useful for diabetes care professionals working with other indigenous groups across the world.
Keywords: Diabetes; ethno-centric; north-east; psycho-social